EVALUATING THE LEVEL OF TERRITORIAL DEVELOPMENT AS AN INFORMATION-ANALYTICAL FOUNDATION FOR CRISIS MANAGEMENT - Гур’єв, Владислав О. (Journal of Strategic Economic Research, 2023)
The relevance of the research topic is determined by the need for effective crisis management through territorial development. In a rapidly changing world and in extraordinary situations such as natural disasters, economic crises, or social conflicts, assessing the level of territorial development becomes an important tool for making informed decisions and developing effective management strategies. Contemporary realities demonstrate that information technologies and analytical methods provide detailed information about the state of territorial development. The application of these tools in the context of crisis management allows for a quick assessment of threats, identification of vulnerable areas, and the development of risk mitigation strategies. The research hypothesis: the assessment of territorial development level as an information-analytical basis will help improve the effectiveness of crisis management and decision-making. The aim of this article is to explore and analyze the assessment of territorial development level as an information-analytical foundation for effective crisis management. To achieve this aim, modern approaches and methods of assessing territorial development and their practical application will be discussed. Different levels of regional development have been identified and diagnosed based ona comprehensive analysis of indicators that include socio-economic and infrastructure parameters. Territories in critical developmental states, characterized by high vulnerability and insufficient resource and infrastructure development, have been identified. Methods and strategies for transitioning out of crisis states have been developed for these identified territories. These approaches include attracting additional investments, improving infrastructure, developing human capital, and implementing special programs and projects. The proposed methods and strategies are aimed at stabilizing and enhancing the development level of crisis-affected territories, ensuring their sustainable and steady recovery. The research confirms that assessing the level of territorial development is a crucial tool for crisis management, enabling the identification and diagnosis of problematic regions and territories. Identifying territories in critical developmental states emphasizes the need for urgent measures and specialized strategies to address their challenges. The developed methods and strategies for exiting crisis states are valuable tools for regional development, strengthening infrastructure, attracting investments, and improving the quality of life for the population. The recommendations and strategies presented can be utilized in the practical activities of government bodies and regional administrations to achieve effective crisis management and sustainable territorial development.